Valorization of biomass derivatives through the conversion of phenol over silica-supported Mo-Re oxide catalysts. (1st January 2020) - Herrera, C.; Ghampson, I.T.; Cruces, K.; Sepúlveda, C.; Barrientos, L.; Laurenti, D.; Geantet, C.; Serpell, R.; Contreras, D.; Melin, V.; Escalona, N.
Graphical abstract: Highlights: Mo-Re catalyst with equal composition produce the highest phenol conversion. Synergistic effect between both Re and Mo oxide species has been reported. Mo-Re catalysts are active due to the formation of oxygen vacancy on the ReOx species. Abstract: Liquid-phase hydrodeoxygenation of phenol over silica-supported MoOx-ReOx catalysts was investigated at 300 °C and 5 MPa of H2 . Mixed-oxides catalysts with similar surface metal density (2.3 atoms of metal per nm 2 of SiO2 ) but different relative Mo and Re loadings were prepared by incipient wetness impregnation. The catalysts were characterized by N2 adsorption, temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), ultraviolet visible diffuse reflectance (UV–vis-DR) spectroscopy, X-ray diffraction (XRD) and temperature programmed desorption of NH3 (TPD-NH3 ). All the catalysts were highly active and selective towards deoxygenated products. However, MoOx/SiO2 was the most selective towards cyclohexane formation. Higher amount of benzene was produced with the Re-containing catalysts than it was over the MoOx/SiO2 catalyst, indicating that ReOx favored direct deoxygenation over hydrogenation of the aromatic ring. The catalyst containing equimolar amounts of MoOx and ReOx exhibited the highest yield of benzene. This result can be attributed to a synergistic effect that arises from electronic interaction between rhenium and molybdenum oxides which favors the formation of new oxygen vacancy sites. The study reveals that benzene selectivity is mainly influenced by ReOx sites and the activity can be tuned by a balance of MoOx and ReOx sites.